Death due to diabetic ketoacidosis: Induction by the consumption of synthetic cannabinoids?. (December 2015) - Hess, C.; Stockhausen, S.; Kernbach-Wighton, G.; Madea, B.
Highlights: Misuse of synthetic cannabinoids can lead to hyperglycaemia. Detection of several synthetic cannabinoids by LC–MS/MS. Biochemical measurements are mandatory for the detection of diabetic ketoacidosis. Abstract: We present a case study on a man who suffered from diabetic ketoacidosis, probably following consumption of synthetic cannabinoids. In blood from a femoral vein AB-CHMINACA, AB-FUBINACA, AM-2201, 5F-AMB, 5F-APINACA, EAM-2201, JWH-018, JWH-122, MAM-2201, STS135 and THJ 2201 could be detected by LC–MS/MS. Diagnosis of ketoacidosis as cause of death was carried out using biochemical measurements of glucose and lactate concentrations in vitreous humour (sum formula: 463 mg/dl) and cerebrospinal fluid (sum formula: 506 mg/dl), of acetone (163 mg/l in femoral venous blood) and of HbA1c (98 mmol/mol). Death due to hyperglycaemia could have been induced by skipping of insulin doses due to his intoxicated state or by the cannabinoids which were described to be able to produce hyperglycaemia themselves.